Effect of Subgrains on the Performance of Mono-Like Crystalline Silicon Solar Cells. (29th October 2013) - Zhou, Su; Zhou, Chunlan; Wang, Wenjing; Tang, Yehua; Chen, Jingwei; Yan, Baojun; Zhao, Yan
Abstract : The application of Czochralski (Cz) monocrystalline silicon material in solar cells is limited by its high cost and serious light-induced degradation. The use of cast multicrystalline silicon is also hindered by its high dislocation densities and high surface reflectance after texturing. Mono-like crystalline silicon is a promising material because it has the advantages of both mono- and multicrystalline silicon. However, when mono-like wafers are made into cells, the efficiencies of a batch of wafers often fluctuate within a wide range of >1% (absolute). In this work, mono-like wafers are classified by a simple process and fabricated into laser doping selective emitter cells. The effect and mechanism of subgrains on the performance of mono-like crystalline silicon solar cells are studied. The results show that the efficiency of mono-like crystalline silicon solar cells significantly depends on material defects that appear as subgrains on an alkaline textured surface. These subgrains have an almost negligible effect on the optical performance, shunt resistance, and junction recombination but significantly affect the minority carrier diffusion length and quantum efficiency within a long wavelength range. Finally, an average efficiency of 18.2% is achieved on wafers with hardly any subgrain but with a small-grain band.